An Evaluation of Studies on the Potential Threats Contributing to the Decline of Eastern Migratory North American Monarch Butterflies (Danaus plexippus) - Wilcox, Alana A. E.; Flockhart, D. T. Tyler; Newman, Amy E. M.; Norris, D. Ryan (Frontiers in Ecology and Evolution, 2019)
The migratory monarch butterflies (Danaus plexippus) of eastern North America have undergone large-scale declines, which may be attributable to a variety of underlying causes. The uncertainty about the primary cause of declines and whether individual threats are likely to increase in the future presents challenges for developing effective conservation management and policy initiatives that aim to improve population viability. This paper identifies five potential threats and classifies these threats according to the types of studies (observational, experimental, simulation/models) and their current impact and anticipated risk. Broadly, the threats can be classified into five categories: (1) change in suitable abiotic environmental conditions; (2) deforestation in the overwintering range; (3) exposure to contaminants including the bacteria Bacillus thuringiensis, herbicides, and insecticides; (4) loss of breeding habitat; and (5) predation, parasitism, and species-specific pathogens. The vast distribution of the monarch butterfly makes it likely that population declines are attributed to a suite of interacting factors that vary spatially and temporally in their contribution. Nonetheless, the published papers we reviewed suggest the decline in suitable environmental conditions in addition to overwintering (i.e., deforestation) and breeding habitat loss are the most likely threats to continue to affect the population viability of monarch butterflies.